Management of rabies - J. Weyer; Lucille Blumberg (South African Family Practice)
Rabies is endemic in South Africa and human rabies cases continue to be reported annually. Most human cases in South Africa are dog-transmitted. Whilst efforts are underway to control and eventually eliminate dog rabies in the country, prevention of the disease through appropriate use of rabies postexposure prophylaxis is critical to save lives. This article provides a summary of rabies in South Africa and key aspects of the prevention of the disease in exposed humans.